Pengaruh Kompetensi Guru PAI Terhadap Akhlak Siswa - Wiwin Winarti Wiwin (Pergunu Jawa Barat, 2022)
The Effect of PAI Teacher Competence on Student Morals at SMP 6 Cibeber and SMP 3 Cibeber. This research is motivated by the problem of less significant changes in student morals for the better in the community environment, which hurts the social environment, both in terms of processes and learning outcomes. PAI Teacher Competence is an important thing that can affect changes in student morals. So that students can apply PAI learning to the real lives of students and encourage students to apply it in their daily lives. This study uses a qualitative approach with a case study method and uses descriptive analysis. Data collection techniques were applied through interviews, document studies and observation (observation)., and documentation studies and observation (observation). The theories and concepts that underlie this research are the learning process, the concept of learning quality and Islamic education. The purpose of this study was to obtain an overview of the influence of PAI teachers' competence on improving students' moral quality. Activities, 1) Planning the learning process to improve the quality of PAI learning, 2) Implementation of Islamic Islamic Studies learning activities to improve the moral quality of students, and 3) activities for assessing the influence of PAI teacher competence to improve students' moral quality, 4) Supporting factors in Islamic Islamic learning to improve quality PAI learning at SMP 6 Cibeber and SMP 3 Cibeber, namely: 1) There is a shared vision, mission, willingness and support from the school principal and all PAI teachers at SMP 6 Cibeber and SMP 3 Cibeber to make every effort to improve the quality of PAI learning at all levels, 2) teacher factor; teachers must have broad insight so that in the management of PAI learning they can create an effective learning atmosphere, 3) The student factor is having an interest in learning, 4). The media factor is having adequate facilities for students. While the inhibiting factors in learning PAI to improve the quality of learning PAI in SMP 6 Cibeber and SMP 3 Cibeber are: The teacher factor, namely, the teacher lacks skills in Islamic education; the student factor, namely students who are less interested in the subject matter, Media factor, namely the lack of utilizing available media or facilities.